Education media development for clutch (EMC) in vocational education: the concept of clutch work - Muhammad Nurtanto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This development research aims to describe the working concept of EMC with VPE valuation method. The EMC quality is based on following aspects: (1) valid according to experts; (2) practical according to practitioners; and (e) effective based on students ability test. The developed cycles and procedures refer to the ADDIE model (analysis, design, development, implementation, and evaluation). Data was collected using rating scale sheet (1-5) and percentage of learning using EMC outcomes. The research results show that the valid and practical aspects of the category are valid and practical enough with an average score of 3.68 (73.6%) and 3.75 (75.0%) respectively. While the results of the effective test obtained an average score of 3.74 (74.8%) and the competence test results is 80.51%. The advantages of EMC are attractive design, practical size, and ease of use (user-friendly). Students recommend that they enjoy learning with EMC and it supports learning about chassis.